(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In the introduction, the researcher tackles importance of research on the game of football, as it ranks first in terms of its popularity because of its characteristics and qualities that increase the enthusiasm of the public, and since this game is refereed by team referees , then referees is considered as an integral part of the game of football . Therefore, it is necessary to take care of them and raise their level. The aim of the study is to recognize the degree of the concentration attention of the first degree field referees and the assistant referees in the outdoor football fields. While the assumption of the study is that there are differences with statistical reference in the degree of the attention concentration . The human domain includes the first degree field referees and the assistant referees in the outdoor football fields in all of the Iraqi governorates .As for the time domain, it is the period of (2020-2021). The place domain includes Al-Shaab International Stadium and the building of the Iraqi Football Federation in the governorate of Baghdad. The method of the study is the descriptive comparative method . The community of the study are chosen deliberately , who are the first degree field referees and the assistant referees in the outdoor football fields from all the Iraqi governorates . They are ( 120 ) referees . In the main experiment the researcher works on (50) field referees and (50) assistant referee . The pilot study includes (20) referees. In order to collect data a questionnaire is used as a study achievement tool. The questionnaire includes (15) statements to be answered by the referee . Results are treated statistically . Results of the study are displayed , analyzed and discussed by the researcher. Results show that the math mean of field referees and the assistant referees is lower than assumed . Results also showed that the degree of the concentration of attention for the field referees is higher than that of the assistant referees . The significance of the study comes from comparing the concentration of attention of the first degree field referees and the assistant referees in the outdoor football fields . Recognizing the degree of the concentration attention , of the first degree field referees and the assistant referees in the outdoor football fields, is also referred to in the problem of the study.The researcher recommends that the Iraqi Football Federation Administration to take such a result in consideration. In addition , it is also recommended that, the aforementioned federation , may concentrate on both financial and moral aspects to stimulate referees in general , and specially the assistant referees , to increase their Psychological capabilities.